Harvesting and Separation Technique of Porphyridium cruentum Polysaccharide Using Ultrafiltration Membrane - Hasanah Hasanah; Iriani Setyaningsih; Uju Uju (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
Red microalga Porphyridium cruentum secreting polysaccharides into its medium culture. Harvestingand separation of polysaccharide of P. cruentum usually use centrifugation and in large scale needs highcost. The use of ultrafiltration membrane can be one of the alternatives for harvesting and separation ofP. cruentum polysaccharide. This study aimed to determine the characteristic of membrane and permeatfrom harvesting and separation of P. cruentum polysaccharide using ultrafiltration. Research consisted offour stages : membrane characterization, cultivation of P. cruentum, harvesting using 0.05 μm ultrafiltrationmembrane, and polysaccharide separation using 0.01 μm ultrafiltration membrane. Characterization ofmembrane permeability and internal resistance on ultrafiltration 0.05 μm dan 0.01 μm were 137.32 L/m2hbarand 62.38 L/m2hbar and 0.01 barm2h/L and 0.02 barm2h/L, respectively. Harvesting using ultrafiltration 0.05μm produced flux 131.37-94.75 L/m2h, biomass rejection 96% and permeate with OD (Optical Density) (0.01± 0.00), viscosity (2.4 ± 0.17 cp), pH (8 ± 0.00), and salinity (42.37 ± 0.11 ‰). Separation of polysaccharideusing ultrafiltration 0.05 μm produced flux 58.11-51.53 L/m2h and permeate with viscosity (2.2 ± 0.30 cp),pH (7.8 ± 0.01), and salinity (38.73 ± 0.05 ‰). Ultrafiltration process decreased OD, viscosity, and salinityof permeate.